Work related stress among nurses in a teaching hospital of Pokhara, Nepal - Chhetri, Rejina; Sunita Gurung (Journal of Gandaki Medical College-Nepal, 2026)
Introduction: Nurses, as the largest and most diverse group of healthcare professionals, often experience significant work-related stress that affects their physical, emotional, and mental well-being, as well as patient care. The objective of this study was to assess the level of work-related stress among nurses in a teaching hospital of Pokhara. Methods: A descriptive cross-sectional research design was adopted for this study which was conducted among nurses working in inpatient department of Gandaki Medical College Teaching Hospital and Research Centre (GMCTHRC), Kaski, Nepal. Probability simple random sampling technique was used to select 123 nurses. Structured standard tool i.e. Expanded Nursing Stress Scale (ENSS) was used for data collection and the data were collected using self-administered structured questionnaire. Descriptive statistics (frequency, percentage, mean, median and standard deviation) and inferential statistics (chi-square test) were used to analyze the data. Results: Among 123 respondents, 48.8% of them had moderate level of stress, 31.7% of respondents had mild stress and 19.5% of respondents had severe level of stress. The level of stress is statistically associated with the age (p=0.026), religion (p=0.012) and working unit (p=0.031). Conclusions: Nurses working in the hospital have some degree of stress. It is essential for hospital administration to identify its underlying causes and implement appropriate stress management strategies.